On a subclass of starlike functions associated with a strip domain - Kumar, S. Sivaprasad; Verma, Neha (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We introduce a new subclass of starlike functions defined as $\mathcal{S}^{*}_{τ}:=\{f\in \mathcal{A}:zf'(z)/f(z) \prec 1+\arctan z=:τ(z)\},$ where $τ(z)$ maps the unit disk $\mathbb {D}:= \{z\in \mathbb{C}:|z|